Global, Regional, and Megacity Trends in the Highest Temperature of the Year: Diagnostics and Evidence for Accelerating Trends. Issue 1 (22nd January 2018) - Papalexiou, Simon Michael; AghaKouchak, Amir; Trenberth, Kevin E.; Foufoula‐Georgiou, Efi
Abstract: Trends in short‐lived high‐temperature extremes record a different dimension of change than the extensively studied annual and seasonal mean daily temperatures. They also have important socioeconomic, environmental, and human health implications. Here, we present analysis of the highest temperature of the year for approximately 9000 stations globally, focusing on quantifying spatially explicit exceedance probabilities during the recent 50‐ and 30‐year periods. A global increase of 0.19°C per decade during the past 50 years (through 2015) accelerated to 0.25°C per decade during the last 30 years, a faster increase than in the mean annual temperature. Strong positive 30‐year trends are detected in large regions of Eurasia and Australia with rates higher than 0.60°C per decade. In cities with more than 5 million inhabitants, where most heat‐related fatalities occur, the average change is 0.33°C per decade, while some east Asia cities, Paris, Moscow, and Houston have experienced changes higher than 0.60°C per decade. Plain Language Summary: Short‐term heatwaves can cause substantial health, economic, and social impacts. They adversely affect animals and plants, and increase the risk of wildfire while inadequate air conditioning may cause human fatalities. Most short‐term heatwaves are associated with a strong anticyclone, and often with dry conditions, but they are clearly exacerbated by global warming from human‐induced climate change. Other effects, such as intensified urbanization can also add to the risks. This paper analyzes the observed highest temperatures that occur every year at nearly 9000 stations, and how they are changing over time and especially over the past 50 and 30 years. We find these short‐term heatwaves to be increasing in most places, especially Eurasia and Australia, and also in megacities. Key Points: The highest temperature of the year increased faster than the mean annual temperature over the past 30 years Most megacities show accelerated warming and a large region in Eurasia shows alarming warming trends Exceedance probabilities of observed 50‐ and 30‐year warming trends are, in most cases, highly unlikely under natural climate variability